Pulse-echo ultrasonic testing of adhesively bonded joints in glass façades - Mojškerc, Bor (Strojniški vestnik, 2016)
This article presents a pulse-echo ultrasonic method of evaluation of adhesively bonded joints in glass façades by means of the amplitudes of reflected ultrasonic signals. Glass façade specimens consist of three basic components: hardened glass, polysulfide or silicone adhesive and a polymer profile. Each component has its own specific acoustic impedance, which relates to a difference in the ultrasound reflection and transmission coefficients. Several glass façade specimens containing defects like air pockets, grease and duct tape are analysed. Measurements are carried out using a normal incidence piezoelectric transducer. Experiments are performed on several adhesively bonded joints in order to detect the defects in the glass-adhesive and adhesive-polymer profile interfaces. Most of the defects, except smaller areas of grease, can be successfully detected. The experimental results suggest that pulse-echo ultrasonic testing is a reasonable way of evaluating of adhesively bonded joints in glass façades.
Keywords: akustična impedanca; impulzno-odbojna metoda; lepljeni spoji; nadzor kakovosti; neporušne preiskave; steklene fasade; ultrazvočne preiskave